Effectiveness of the multidimensional ergonomic intervention model to reduce musculoskeletal discomfort among street sweepers in Chiang Rai Province, Thailand - Pintakham K; Siriwong W (Dove Medical Press, 2016)
Kanjanar Pintakham,1,2 Wattasit Siriwong1 1College of Public Health Sciences, Chulalongkorn University, Bangkok, 2School of Health Science, Chiang Rai Rajabhat University, Chiang Rai, Thailand Abstract: The aim of this study was to evaluate the effectiveness of multidimensional ergonomic intervention (MEI) model to reduce musculoskeletal discomfort (MSD) among street sweepers. A quasi-experimental study was conducted in Chiang Rai Province. The MEI model was designed on the basis of four core components: cognitive behavior therapy, ergonomic education training, stretching exercise, and the foam sleeve broom handle grip. Seventy-five street sweepers volunteered for the screening process on MSD of having level score ≥4 by physiotherapist. Face to face interviews were used mainly in order to diagnose MSD. Physical examination was performed by physiotherapist and physical performance by sports scientist. The findings showed that the MEI model among the intervention group significantly reduced MSD compared with that among control group at exit model and follow-up (P<0.01). This research suggests that the MEI model was appropriate to reduce MSD associated with repetitive movement and awkward postures on task. Keywords: repetitive movement, cognitive behavior therapy, stretching exercise, street sweepers